Perancangan Gasifikasi Downdraft dengan Variasi Laju Aliran Oksigen sebagai Agen Gasifikasi - Gusti Ngurah Agung Satria Prasetya D.Y; Made Sucipta; I Nyoman Suprapta Winaya (Program Studi Magister Teknik Mesin Universitas Udayana, 2015)
Abstract Biomass energy is energy derived from biological material from plants such as wood, rice husk, corn head, and other The process of conversion of biomass into energy can be process by combustion, pyrolysis, and gasification. The gasification process is a process of utilization of biomass by converting energy from a solid raw material (biomass) into syn-gas (the synthesis gas) that can later be used as fuel. One example of gasification that has been developed is a downdraft system. Gasification process has several factors that affect the process and content of syngas dihasillkannyaie, characteristics of biomass gasifier designs, types of agents gasifikasinya, and the air-fuel ratio. In this study the gasification reactor is designed to use black steel pipe diameter of 6